2006
DOI: 10.1186/1472-6793-6-6
|View full text |Cite
|
Sign up to set email alerts
|

An immune response in the bumblebee, Bombus terrestris leads to increased food consumption

Abstract: BackgroundThe concept of a costly immune system that must be traded off against other important physiological systems is fundamental to the burgeoning field of ecological immunity. Bumblebees have become one of the central models in this field. Although previous work has demonstrated costs of immunity in numerous life history traits, estimates of the more direct costs of bumblebee immunity have yet to be made.ResultsHere we show a 7.5% increase in energy consumption in response to non-pathogenic immune stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 23 publications
(26 reference statements)
0
16
0
Order By: Relevance
“…First, in accordance with the bibliography for vertebrates, it was found that LPS produces anorexia in the locust (Goldsworthy, 2010 ). Second, the opposite effect has been reported in bumblebees, as they increase their food intake (Tyler et al, 2006 ). Finally, in honey bees, sucrose intake was measured for an extended period of a week after LPS injection and no change was found (Köhler et al, 2012 ).…”
Section: Discussionmentioning
confidence: 95%
“…First, in accordance with the bibliography for vertebrates, it was found that LPS produces anorexia in the locust (Goldsworthy, 2010 ). Second, the opposite effect has been reported in bumblebees, as they increase their food intake (Tyler et al, 2006 ). Finally, in honey bees, sucrose intake was measured for an extended period of a week after LPS injection and no change was found (Köhler et al, 2012 ).…”
Section: Discussionmentioning
confidence: 95%
“…Neonicotinoids are, like anabasine and nicotine, acetylcholine receptor agonists, so it is logical that each of these compounds would have similar effects on bees. Chemical exposure may directly suppress immunity [ 94 , 96 ], and the combined stresses of chemical exposure and infection may result in trade-offs between immunity and detoxification, both of which are energetically expensive [ 38 , 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…B 282: 20151371 the natural environment is widespread. It may also be expected that infected bees could have increased flower handling times and foraging demands owing to the cognitive and energetic costs of infection which would drive parasite dispersal rate even higher [49][50][51][52][53]. The propensity of a parasite to transfer between pollinator and flower is remarkably high, with clear vectoring between foraging sites taking place very rapidly.…”
Section: Discussionmentioning
confidence: 99%